Źródła i formy kontaktów z bliskimi mężczyzn odbywających karę pozbawienia wolności - Jarzębińska, Aneta; Iwański, Rafał; Leszko, Magdalena (Kultura-Społeczeństwo-Edukacja, 2021)
Social support is essential for mental and physical health and plays an important role in reducing the risk of returning to prison. The main sources of prisoners’ social support are relatives with whom they have the right to communicate using a variety of forms. The frequency of contact depends on the type of prison. However, little research examines prisoners’ communication with their relatives. The study was conducted on 478 men between the ages of 16 and 68 (M = 35,2; SD = 9,7), who were serving a prison sentence in one of five penitentiary facilities. The analysis revealed that the majority of incarcerated men had contact with their relatives, usually in a form of phone calls. The majority of them had contact with a mother. The study also demonstrated that the percentage of contacts with relatives decreased with age and time spent in prison.